1993
DOI: 10.1007/bf02246968
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and nicotine improve visual tracking by rats: a comparison with amphetamine, cocaine and apomorphine

Abstract: Psychomotor stimulant drugs such as caffeine, nicotine, amphetamine and cocaine, have been shown to improve vigilance in man under conditions of fatigue. Nicotine has also been shown to improve performance in some cognitive tests in patients with Alzheimer's disease. In rodents these drugs increase activity which may confound "performance enhancing effects" in rodent models. However, improvements have been found in a number of tests that do not seem to be directly dependent upon an enhancement of locomotor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The results of the present experiment and of previous studies (Evenden and Robbins 1985;Grilly and Gowans 1988;Grilly et al 1989;Grilly and Grogan 1990;Grilly and Nocjar 1990;Grilly 1992;Evenden et al 1993;Grilly and Simon 1994;Grilly and Pistell 1997) indicate that there are a variety of conditions under which psychostimulants such as amphetamine and cocaine may enhance the choice performance of normal, non-fatigued adult animals in visual stimulus detection tasks. In general, these findings are consistent with the conclusions from studies with humans that psychostimulants can improve overall level of performance (both accuracy and speed) in vigilance-dependent tasks (Koelega 1993).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The results of the present experiment and of previous studies (Evenden and Robbins 1985;Grilly and Gowans 1988;Grilly et al 1989;Grilly and Grogan 1990;Grilly and Nocjar 1990;Grilly 1992;Evenden et al 1993;Grilly and Simon 1994;Grilly and Pistell 1997) indicate that there are a variety of conditions under which psychostimulants such as amphetamine and cocaine may enhance the choice performance of normal, non-fatigued adult animals in visual stimulus detection tasks. In general, these findings are consistent with the conclusions from studies with humans that psychostimulants can improve overall level of performance (both accuracy and speed) in vigilance-dependent tasks (Koelega 1993).…”
Section: Discussionmentioning
confidence: 65%
“…Whether choice task performance is facilitated or disrupted by psychostimulants may also depend on the degree to which the animal's behavior is adequately controlled by the stimulus-reinforcement contingencies of the task before drug testing, i.e., well-trained performance, under strong stimulus control, is more likely to be improved with low doses of psychostimulants (Lyon and Robbins 1975;Grilly 1977;Robbins and Sahakian 1983;Grilly and Nocjar 1990;Evenden et al 1993). On the other hand, if the contingencies between the stimuli, the choice behavior(s) and reinforcers are not well established prior to testing, irrelevant behaviors activated by psychostimulants, e.g., general motor activity, may increase and compete with the reinforcement-contingent behavior.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…than after the lower (1-30 mg/kg) doses of caffeine because of stress induced by the higher caffeine dose. To test this possibility would require a more precise definition of ''arousal'' and carefully designed behavioral tests that would allow differentiation of multiple aspects of arousal (e.g., Evenden et al, 1993). Despite these conceptual problems, however, the response to stress may involve an increase in certain aspects of arousal, and therefore, some of the Fos expression seen at 75 mg/kg may be related to stress-induced arousal.…”
Section: Relationship Between Caffeine-induced Fos Immunoreactivity Amentioning
confidence: 96%
“…Recently, some enhancement in performance has been detected with nicotine as indexed by increases in response accuracy and/or speed (Mirza and Stolerman 1998;Blondel et al 2000;Grottick and Higgins 2000), although these effects were not dosedependent, and were only found under specific task conditions. For amphetamine, other tests of vigilance in rats have detected either performance disruption (McGaughty and Sarter 1995) or improvements (Evenden et al 1993), whilst in the 5-CSRTT, performance improvement has been restricted to increases in response speed Robbins 1987, 1989). It has been suggested that the relatively low demands in processing required for these tasks result in high levels of performance, thus rendering them insensitive to various manipulations (Moore et al 1992).…”
Section: Introductionmentioning
confidence: 97%